THE DEVELOPMENT OF THE SNAKE AND LADDER GAME AS A MEDIUM FOR PRACTICING HIGH SCHOOL PHYSICS QUESTIONS ON THE TOPIC MECHANICS AND FLUIDS - Permana, A. H.; Muliyati, D.; Halim, J. O. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2024)
Abstrak A joyful learning approach is able to generate student learning motivation which in turn can improve student learning outcomes (M Kamelia et.al, 2017). One of joyful learning approach is the use of educational games. This study developed a game of snakes and ladders as a medium for practicing Physics questions. This study used the 4D development method. The developed game was assessed by experts (evaluation experts, media experts, and software engineering experts) using a Likert scale quessionnaire. The results of the validation of the developed game were obtained 93,18% by evaluation experts, 100% by media experts and 87,5% by software engineer experts. While the results of trials on high school teachers and students reached 76,04% and 83%. From these results it can be stated that the game developed is very suitable for use in learning activities and is beneficial for teachers and students. Kata-kata kunci: Ladder game, Topic Mechsnics, fluids.